Os camponeses e a mobilização popular: igreja católica, saques e movimentos sociais em Itapiúna/CE (1980-1993) - Pereira, Francisco Ruy Gondim (2008)
During the 1980s social movements born from the pastoral activity of the Catholic Church in the city of Itapiúna, Ceará’ began to “offer” their mobilization resources to rural workers protesting the inefficiency of state authorities to provide support during long periods of economic recession. More than just an “offer” of assistance, the actions of Catholic activists, realizing the power of protest and the political implications of the movement inspired massive pillaging throughout the region. Social movement leaders sought to “organize” and “politicize” the act of pillaging as means of contesting and transforming the basic societal relations of the masses of impoverished rural workers. Rather than demanding the return of traditional relations based on notions of a “moral economy” i.e. paternalist state action in relation to the poor, the movement began to question prevailing social hierarchies and contest the longstanding paternalist nature of state assistance. The fundamental objective of this study is to examine the process of mobilization and social protest in Itapiúna, Ceará’ and their relationship to the social upheavals of the 1980s and 1990s. My research will focus specifically on the intersection of mobilization articulated by local social movements and the direct action of rural workers, an intense process that melded notions of “social transformation” and the “moral economy” as a platform that either motivated or legitimized massive pillaging.